2011
DOI: 10.1017/s0007114511001425
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil supplemented with menaquinone-7 significantly affects osteocalcin carboxylation

Abstract: Menaquinone-7 (MK-7), a member of the vitamin K 2 family, performs several functions, all related to its recognised effect on posttranslational carboxylation of certain protein-bound glutamate residues. Due to its lipophilic structure MK-7 is soluble in olive oil, so the aim of the present study was to test whether extra-virgin (EV) olive oil enriched with MK-7 significantly increases MK-7 plasma levels and has an effect on osteocalcin and its carboxylation status. Healthy young volunteers (n 12) were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…This is in-line with previous published works, which indicated nutritional doses of MK-7 (45–90 μg/day) to be effective for carboxylation of osteocalcin [16,17]. …”
Section: Discussionsupporting
confidence: 92%
“…This is in-line with previous published works, which indicated nutritional doses of MK-7 (45–90 μg/day) to be effective for carboxylation of osteocalcin [16,17]. …”
Section: Discussionsupporting
confidence: 92%
“…However, data are limited, since the HPLC and MS techniques are limited to a few qualified laboratories and the long-chain menaquinones are often below the detection limit in the circulation when measured in the general population. Only a few studies have measured plasma menaquinones in response to the intake of individual menaquinones, and these have been limited to MK-7 or MK-4 supplementation ( 13 , 27 , 54 ) . For plasma MK-7, two studies showed a clear dose–response effect on circulating MK-7 concentrations after supplementation with doses ranging between 45 and 420 μg ( 13 , 54 ) .…”
Section: The Amount Of Menaquinones Required To Prevent Deficiency Anmentioning
confidence: 99%
“…Only a few studies have measured plasma menaquinones in response to the intake of individual menaquinones, and these have been limited to MK-7 or MK-4 supplementation ( 13 , 27 , 54 ) . For plasma MK-7, two studies showed a clear dose–response effect on circulating MK-7 concentrations after supplementation with doses ranging between 45 and 420 μg ( 13 , 54 ) . In contrast, MK-4 was not detected in the circulation following a single dose of 420 μg ( 27 ) .…”
Section: The Amount Of Menaquinones Required To Prevent Deficiency Anmentioning
confidence: 99%
“…14,15 Several studies have examined the effect of MK-7 supplementation on the carboxylation of OC and MGP; this research has found a dose-dependent relationship between the quantity of MK-7 and the carboxylation of OC and MGP. [15][16][17][18][19][20] The daily amount of MK-7 required to influence carboxylation of OC and MGP has been found to vary from 45 µg to 360 µg. [15][16][17][18][19][20] This effect is believed to have clinical significance due to the role that these proteins play in bone and the cardiovascular system.…”
Section: Menaquinone Supplementationmentioning
confidence: 99%
“…[15][16][17][18][19][20] The daily amount of MK-7 required to influence carboxylation of OC and MGP has been found to vary from 45 µg to 360 µg. [15][16][17][18][19][20] This effect is believed to have clinical significance due to the role that these proteins play in bone and the cardiovascular system. High levels of dephospho-uncarboxylated MGP (du-MGP) and uncarboxylated OC (uOC) have been associated with arterial stiffness and an increased risk of fractures.…”
Section: Menaquinone Supplementationmentioning
confidence: 99%